SELECTED PROBLEMS OF RISK EVALUATION OF CHANGE IN CERTIFIED CIVIL AVIATION ORGANISATIONS - Telesfor Marek MARKIEWICZ; Piotr MAKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
This article presents some of the generalised results of this research conducted in the form of a diagnostic survey among Safety Managers and a review of safety risk management procedures, including the rules of change risk evaluation, applied in selected civil aviation organisations subject to the survey. This publication aimed to put them under the discussion of experts interested in the issues. Important problems resulting from the necessity to meet general guidelines standardising processes of risk management, formulated in international law regulations [2], as well as in advisory materials of the International Civil Aviation Organisation [6-8], and others [3, 4], including national ones [11], in confrontation with the need for their practical application, were described. Concerning the general rule of risk evaluation described there, inconsistencies in interpretation of the scale of probability and frequency indices and their influence on the evaluation context were pointed out. A model, considering the time aspect in Event Tree Analysis - ETA procedures based on [5, 9], was proposed. Perceived threats to the results of change risk evaluation caused by applying the "the worst foreseeable situation" principle were described. A different approach in the evaluation of change risk based on a comprehensive assessment of the impact of all identified risks on the defined effect was also proposed. Proposals were made to eliminate the disadvantage resulting from the definition of the probability index value – "extremely improbate".